Separation of Escherichia coli penicillin-binding proteins into different membrane vesicles by agarose electrophoresis and sizing chromatography. - Leidenix, M J (1989)
Membrane vesicles from the envelope of Escherichia coli were separated by electrophoresis through dilute agarose and by sizing chromatography through Sephacryl S-1000. These techniques revealed that proteins were associated with different subsets of vesicles. In particular, dilute agarose electrophoresis clearly separated the inner membrane penicillin-binding proteins (PBPs) into different vesicle groups. Vesicles containing PBPs 4, 6, 7, and 8 migrated rapidly through agarose; vesicles with PBPs 1a, 1b, 2, 3, and 5 eluted later. With the exception of PBP 4, which migrated with PBPs 1 through 5, chromatography through Sephacryl S-1000 was able to distinguish the same two vesicle sets, though the extent of separation was poorer than with agarose. The existence of these associations among vesicles and proteins suggests that there is an organization to the inner membrane of E. coli which is not observed when membrane vesicles are separated solely on the basis of density in sucrose gradients.